Essential Oils of Zingiber Species from Vietnam: Chemical Compositions and Biological Activities - Huong, Le Thi (Plants (Basel), 2020)
Mosquito-borne diseases are a large problem in Vietnam as elsewhere. Due to environmental concerns regarding the use of synthetic insecticides as well as developing insecticidal resistance, there is a need for environmentally-benign alternative mosquito control agents. In addition, resistance of pathogenic microorganisms to antibiotics is an increasing problem. As part of a program to identify essential oils as alternative larvicidal and antimicrobial agents, the leaf, stem, and rhizome essential oils of several Zingiber species, obtained from wild-growing specimens in northern Vietnam, were acquired by hydrodistillation and investigated using gas chromatography. The mosquito larvicidal activities of the essential oils were assessed against Culex quinquefasciatus, Aedes albopictus, and Ae. aegypti, and for antibacterial activity against a selection of Gram-positive and Gram-negative bacteria, and for activity against Candida albicans. Zingiber essential oils rich in α-pinene and β-pinene showed the best larvicidal activity. Zingiber nudicarpum rhizome essential oil showed excellent antibacterial activity against Enterococcus faecalis, Staphylococcus aureus, and Bacillus cereus, with minimum inhibitory concentrations (MIC) of 2, 8, and 1 μg/mL, respectively. However, the major components, α-pinene and β-pinene, cannot explain the antibacterial activities obtained.